Electronic, bonding and optical properties of the LiGaGe2X6 (X = S, Se, and Te) compounds: An ab initio study - Azzi, O.; Hacene, F. Boukli; Ferouani, Abdel Karim; Ouahrani, Tarik; Reshak, Ali Hussain (Elsevier, 2019)
In order to gain an insight into the bonding and to characterize linear and nonlinear optical properties of three infrared LiGaGe2S6, LiGaGe2Se6, and LiGaGe2Te6 compounds, we performed an ab initio calculation based on density functional theory. The calculations determined lattice parameters, band gaps, dipole moments, and second harmonic components that commonly agreed well with the available experimental data. We show in this article, through a large body of calculations, the trend in the row of participating anions, S ⟶ Se ⟶ Te, enhances the polarization effect and the coordination structure distortions in the polyhedra groups forming the bonding pattern of the cell. This one also affects both the electronic and the optical properties, making the compounds more propitious for device-based optical applications.